Mapping the disparities in intimate partner violence prevalence and determinants across Sub-Saharan Africa - Tilahun B. Mossie; Haile Mekonnen Fenta; Meseret Tadesse; Animut Tadele (Frontiers Media S.A., 2023)
ObjectiveThis study aimed to map disparities in prevalence and associated factors across countries in Sub-Saharan Africa.MethodsWe used National Demographic and Health Survey (DHS) data from 26 countries in the region with 114,340 participants. Women and girls in the reproductive age group of 15 to 49 years were included in the study. To map disparities across countries and their provinces, we employed the kriging interpolation technique. We used STATA for data management.ResultThe prevalence of physical, emotional and sexual IPV in Sub-Saharan Africa was 30.58, 30.22, and 12.6% respectively, and at least one form of IPV was 42.62%. Disparities were observed across the countries and provinces in each country. Younger age, secondary-level education and above, moderate participation in decision-making, not working out of home, not afraid of the spouse, rich (wealth index), not having a child, high maternal literacy, and rural residence relatively decreased the odds of IPV. The husbands' lower education, alcohol consumption, and high controlling behavior increased the probability of IPV.ConclusionThe prevalence of Intimate Partner Violence in Sub-Saharan Africa is the highest in the world, a signal that the global agenda to end all forms of violence against women will be difficult to achieve. There is a large gap across countries and provinces in each country. Area-specific intervention packages that focus on modifiable factors should be strengthened.